Dedifferentiated Liposarcoma of the Ileal Mesentery – Case Report - James, Jerin; George, Johan; Kumar, Sathish R; C, Ramesan (Indian Journal of Case Reports, 2025)
Primary mesenteric dedifferentiated liposarcoma (DDLPS) is an extremely rare malignancy, usually arising in the retroperitoneum. Its occurrence in the mesentery presents significant diagnostic and therapeutic challenges. We report a 58-year-old female with progressive abdominal distension and left-sided pain for 6 months. Imaging revealed an intra-abdominal mass and exploratory laparotomy identified a large mesenteric tumor, which was completely excised with negative microscopic margins (R0 resection). Histopathology confirmed DDLPS, with immunohistochemical analysis showing MDM2 and CDK4 positivity, DDLPS in the mesentery is challenging to diagnose due to its rarity and diverse histological presentation. Surgical excision remains the primary treatment, but the tumor’s high recurrence rate necessitates long-term follow-up and possible adjuvant therapy. Targeted treatments, such as MDM2 and CDK4 inhibitors, may offer additional options. This case underscores the importance of a multidisciplinary approach in diagnosing and managing rare mesenteric malignancies, emphasizing the need for vigilant surveillance and individualized treatment planning.